Pengaruh Etos Kerja Islami, Motivasi Kerja, Kompensasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Nur Halizah (ITB AAS INDONESIA Surakarta, 2023)
Improved employee performance is in line with the need to improve the quality of sustainable development plans at BAPPEDA. Using studies on employees at BAPPEDA Kota Probolinggo, this research reveals the importance of improving employee performance to achieve quality planning, research and development policies. The purpose of this study is to describe the influence of Islamic work ethic, work motivation, work environment, and rewards on employee performance with job satisfaction as an intervening variable. The approach used is a quantitative approach. The total population is all BAPEDDA employees which has a total of 67 people. 55 samples were taken using saturated samples and purposive samples. The data analysis used is SPSS and the data is processed using path analysis. The results of this study are two interrelated patterns, the first is the Islamic work ethic, and compensation has a negative effect on job satisfaction. while work motivation and work environment have a positive influence on job satisfaction. Second, the Islamic work ethic, work motivation, and work environment have a positive influence on employee performance, while compensation has a negative effect on employee performance, and job satisfaction has a positive effect on employee performance. Keywords : Islamic Work Ethic, Work Motivation, Work Environment, Compensation, Performance, Satisfaction.